Pemanfaatan Limbah Kotoran Ayam sebagai Bahan Baku Pupuk Cair Alami di Kabupaten Simalungun - Halim Simatupang; Rudi Salman; Taufik Hidayat; Irfandi Irfandi (Universitas Mathla'ul Anwar Banten, 2020)
UTILIZATION OF CHICKEN MANURE WASTE AS RAW MATERIAL FOR NATURAL LIQUID FERTILIZER IN SIMALUNGUN REGENCY. In the economic activities of the chicken farmers and farmers community groups fail to get adequate profits to survive because of the many problems that occur in the Group Production process because the waste processing is not right, causing problems in the business and disrupt the surrounding environment. The high costs of agricultural production and fertilizer make agricultural production also has a downward effect. In addition, other problems include: 1) The low income of the Group due to the decline in livestock and agriculture production due to waste; 2) Livestock waste is not utilized so it becomes a pollutant in the community; 3) Lack of community and group members' understanding of the use of livestock manure and agricultural waste as raw material for liquid organic fertilizer; 4) Limited public knowledge about processing liquid organic fertilizer; 5) Unavailability of TTG maker of liquid organic fertilizer. The sequence of implementation of activities as a Solution is 1) To increase the income of community groups is done through the manufacture of liquid organic fertilizer from chicken manure and agricultural waste and Appropriate Technology (TTG); 2) Provide training in making liquid organic fertilizer to community groups 3). Solutions to provide understanding to the Group for the manufacture of liquid organic fertilizer from chicken manure and agricultural waste; 4) Provide workshops and business management assistance in making liquid fertilizer; 5) Provide assistance in making liquid organic fertilizer from chicken manure and agricultural waste. Target outputs of the program include guide to the method of making Liquid Organic Fertilizers, production of liquid orgamic fertilizer with quality and quantity that meets the standard, and providing and Socializing Appropriate Technology Tools for making liquid organic fertilizer from chicken manure and agricultural waste.